Management Strategies for Monocrystalline SiC Substrate Production Lines under Downtime Disturbances - Zhu, Xisheng; Zhang, Dan; Ai, Wenhao; Fu, Weidong; Zuo, Dunwen (2022 International Conference on Automation, Robotics and Computer Engineering (ICARCE), 2022)
In order to reduce the system performance loss and restore the normal operation for the downtime disturbance event on the monocrystalline SiC substrate production line, a prediction model of the performance of the SiC wafer substrate production line is established based on the G/G/m/b queuing model. A production line simulation model is built in the Witness simulation software to verify the feasibility of the prediction model. A production line performance optimization model under downtime disturbance with the buffer capacity and processing preparation time as optimization parameters is established combining with the concept of time window. And the management strategy is obtained by the optimization solution of the model using genetic algorithm. The feasibility of the proposed method is verified based on the improved coupled map lattices production network propagation model. The results of the simulation validation in Witness software show that the proposed method improves the production performance of the production line under equipment downtime.